Work Ability, Civil Servants (PNS), Government Employees with Work Agreements (PPPK), Bima Regency Social Service - Refi, Refi; Badar , Muhammad; Aprianti, Kartin (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine whether there is a significant difference in work ability between Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) at the Bima Regency Social Service. This research was motivated by several issues related to work ability among PNS and PPPK, including limited mastery of information technology and government digital systems among some PNS, as well as difficulties among some PPPK in adapting to organizational work culture, administrative procedures, and bureaucratic mechanisms. This study employed a comparative research design. The population consisted of 69 employees, comprising 38 PNS and 31 PPPK. The sample consisted of 62 respondents, including 31 PNS and 31 PPPK. Data were collected through observation, questionnaires, and literature review. The research instrument used a Likert scale questionnaire ranging from 1 to 5. Data analysis techniques included validity testing, reliability testing, homogeneity testing, and a difference test using One-Way ANOVA. The results showed that all questionnaire items were valid and reliable. The average work ability score of PNS was 38.94, while the average score of PPPK was 57.29. The One-Way ANOVA results showed an F value of 3.296 with a significance value of 0.009, indicating a significant difference in work ability between PNS and PPPK at the Bima Regency Social Service. Based on the average scores, PPPK demonstrated higher work ability than PNS. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected.